2022
DOI: 10.1590/1678-5150-pvb-6940
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the dog (Canis lupus familiaris) in cocoa farms as carriers of helminths potentially transmissible to humans and wildlife in the Southern Bahia, Brazil

Abstract: Domestic dogs (Canis lupus familiaris) can be considered an invasive species as they have been introduced by humans in different parts of the world and represent a risk to wildlife conservation. Large extensions of agroforestry systems, where cocoa is grown under the shade of native trees, contribute to wildlife conservation in southern Bahia, Brazil. However, this system can increase contact between species of the native fauna and domestic dogs, which are frequently taken to the fields by rural workers. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…The prevalence of gastrointestinal parasites in dogs reported here, mainly hookworms and Toxocara sp., is in line with the findings of other studies that have demonstrated the need for a surveillance program in Brazil, along the lines of One Health concept, for the prevention of zoonotic diseases transmitted by dogs that circulate between domestic and wild areas, in order to avoid possible spillover events (Dantas-Torres & Otranto, 2014;Curi et al, 2017;Silva et al, 2022;Winck et al, 2022).…”
Section: Coproparasitological Examination Of Domestic Dogssupporting
confidence: 90%
See 4 more Smart Citations
“…The prevalence of gastrointestinal parasites in dogs reported here, mainly hookworms and Toxocara sp., is in line with the findings of other studies that have demonstrated the need for a surveillance program in Brazil, along the lines of One Health concept, for the prevention of zoonotic diseases transmitted by dogs that circulate between domestic and wild areas, in order to avoid possible spillover events (Dantas-Torres & Otranto, 2014;Curi et al, 2017;Silva et al, 2022;Winck et al, 2022).…”
Section: Coproparasitological Examination Of Domestic Dogssupporting
confidence: 90%
“…Although it has no known zoonotic potential, the nematode T. vulpis is among the most prevalent helminth parasites of domestic dogs with significant frequencies (Figure 2). The notable prevalence of this parasite in dogs is found in other similar studies (Silva et al, 2022;Souza et al, 2023;Ugalde et al, 2023).…”
Section: Coproparasitological Examination Of Domestic Dogssupporting
confidence: 75%
See 3 more Smart Citations